Volatile Memories: Personal Data and Post Human Subjectivity in The Aspern Papers, Analogue: A Hate Story and Tacoma. Issue 7 (15th April 2019) - Gallagher, Rob
Contemporary narrative video games still owe a debt to notions of plotting and characterization inherited from realist novels, even as they demonstrate how digital technologies are driving the development not merely of new fictional forms but also new conceptions of identity and subjectivity. This article expands upon these claims through analyses of three texts. Published in 1888 and revised in 1908, Henry James's novella The Aspern Papers follows a protagonist obsessed with laying his hands on a long-dead Romantic poet's archive; released in the 21st-century, Christine Love's (2012) Analogue: A Hate Story and Fullbright's (2017) Tacoma imagine technologically advanced posthuman futures in order to pose questions about datafication, identity, and the terms on which the past remains accessible in the present. Considered together, they shed light on longer generic traditions, the relationship between literature and video games, and the ethical and epistemological issues raised by new technologies.